PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA SUBTEMA MANUSIA DAN BENDA DI LINGKUNGANNYA - Permatasari, Shalsa Dwi; Tustiyana Windiyani; Dendy Saeful Zen (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Shalsa Dwi Permatasari, 037118075. The Effect of the Problem Based Learning Model on Student Learning Outcomes in the Sub-theme of Humans and Things in Their Environment. Thesis for Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Pakuan University, 2023. This study used a quasi-experimental research type with a two-class design. The purpose of this study was to determine the effect of the Problem Based Learning model on learning outcomes for the Sub-theme of Humans and Objects in their Environment. The subjects of this study were students in grades V-A and V-B of Benda State Elementary School, Sukabumi Regency, even semester of the 2022/2023 academic year, with a total of 66 students. The results showed that there was a significant difference in the average value of N-Gain and completeness in the learning outcomes of the experimental class (Problem Based Learning) and the control/conventional class (Discovery Learning). The average N-Gain score in the experimental group was 61.24 with 94% completeness, while the average N-Gain in the control class was 43.00 with 69% completeness. The results of the hypothesis test stated that Ho was rejected and Ha was accepted, because tcount (2.1038) > ttable (1.81072) with dk 64 and a significance level of 0.05 (5%). Based on the results of this study, it can be concluded that there is an effect of applying the Problem Based Learning model to learning outcomes for the Sub-theme of Humans and Things in Their Environment in class V Benda State Elementary School, Sukabumi Regency, Even Semester for the 2022/2023 school year.